Measuring Poverty Based On Multidimensional Poverty Index (MPI) in Dampit District - Marco Juan Aristo; Ismu Rini Dwi Ari; Gunawan Prayitno (Perencanaan Wilayah dan Kota FT UB, 2026)
Poverty is a complex and multidimensional phenomenon that cannot be sufficiently measured solely through income or expenditure approaches. This research is essential because poverty is often narrowly perceived as purely economic issue that related to income and expenditure, whereas it is actually a far more complex phenomenon that extends beyong mere financial figures. This study aims to measure poverty using the Multidimensional Poverty Index (MPI) in Dampit District. Introduced in 2010, the MPI captures poverty through three key dimensions: education, health, and living standards. The multidimensional perspective allows for the identification of specific indicators that reflect the various deprivations and limitations experienced by the poor. The research was conducted in Dampit District, which is noted as the second-highest recipient of BPNT and PKH, as well as the second-highest number of poor households in Malang Regency. Data were collected through questionnaires distributed to 346 households across 12 villages, proportionally divided into poor and non-poor household groups. MPI measurements in Dampit District are classified into four levels: very low, low, medium, and high. The study identified three villages with high MPI scores: Sukodono Village (0.301), Srimulyo Village (0.271), and Baturetno Village (0.276). Only one area, Dampit Village (0.059), categorized as very low, serves as the district's administrative center. The dimensions of education and living standards significantly contributed to the deprivations found across the villages. The findings of this research are expected to serve as a foundation for formulating poverty alleviation policies and prioritizing development strategies based on MPI dimensions.